Group decision making of fixed offshore platform decommissioning in Indonesia - Sidiq, Rizky Bahtiar; Utomo, Christiono; Silvianita, Silvianita (Edelweiss Applied Science and Technology, 2025)
The selection of decommissioning methods should consider several essential points such as costs, stakeholders, availability of tools, and the environment. Due to the relatively significant cost challenges, the complexity of stakeholder issues, and the fact that several offshore fixed platforms are no longer operational, the development of decommissioning in Indonesia has yet to match these challenges. The objective of this study is to facilitate decision-making in the decommissioning of fixed offshore platforms based on group decision-making using the Analytical Hierarchy Process (AHP). Several questionnaires with numerical score values were provided to experts to perform pairwise comparisons of the criteria and alternatives related to decommissioning for further analysis using the AHP method. The results for the decommissioning alternatives showed different tendencies for each stakeholder, owing to their contrasting interests. However, all stakeholders agreed that the cost of decommissioning was a crucial factor in deciding the method. As a result of using the AHP method, the leave-in-place alternative was identified as the best decommissioning method, considering various aspects such as cost, socioeconomic factors, engineering, health and safety, and environmental impact. For future research, a more in-depth analysis of each criterion can be conducted.